Development of Information Website for PAUD Al Lathifiyah IV as PAUD Promotion Media and School Profiles - Suci Nurfauziah (Teknodika, 2021)
The website is a medium for delivering information and online promotional media that the broader community can access. Generally, every school should have a website as a complete school profile. However, so far, the information and promotion of PAUD Al Lathifiyah IV Lamongan have only been limited to word of mouth (WOM) through local people. This study aims to develop the PAUD Al Lathifiyah IV website as a promotional media and school profile. Implementation of PAUD website used CMS WordPress. Based on the research results, the PAUD Al Lathifiyah IV website could be applied and run well and was responsive on all browser devices. With the PAUD Al Lathifiyah IV website, the way of delivering information and promotions was more effective and accurate than information obtained by word of mouth.